Expert Answers

An illustration of the letter 'A' in a speech bubbles

we need to determine ctg(2x)  if we know that ctg(x)=3

we know that ctg(2x)=1/tan(2x) =1/tan(x+x)

We know that tan(x+y)= (tanx+tany)/1-tanx*tany)

==> 1/tan(x+x)= [1-(tanx)^2]/2tanx

 We know that ctg=3 , then tanx= 1/3

Substitute:

ctg(2x)= 1-(1/3)^2 / 2(1/3)

          = (1-1/9) / (2/3)

          = 8(3)/9(2)= 8/6= 4/3

 

Approved by eNotes Editorial Team
Soaring plane image

We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

  • 30,000+ book summaries
  • 20% study tools discount
  • Ad-free content
  • PDF downloads
  • 300,000+ answers
  • 5-star customer support
Start your 48-Hour Free Trial